The impact of proteins, glycoproteins and fructose in blood and seminal plasma on sperms concentration In infertile men - Nahla M. Al-Sakkal (مجلة كلية الطب, 2009)
Background: proteins, glycoproteins and fructose as parameters used to assess infertility in men. Objective: To determine and correlate serum and seminal plasma of total proteins, glycoproteins and fructose with infertility in men. Patients and Methods: The study was performed on 154 subjects; 109 infertile men (oligospermic and azoospermic) and 45 normal volunteers (normospermic men). All sera and seminal plasma were submitted for total proteins, glycoproteins and fructose levels measurment. Results: No significant difference was noted in serum and seminal plasma of total proteins in oligospermic and azoospermic and that of normospermic men (P>0.05) compared to normospermic men. Statistical significant reduction (P<0.05) was noted in seminal plasma glycoproteins in oligospermic as compared to normospermic and azoospermic men. A significant elevation (P<0.05) of fructose levels were observed in seminal plasma of azoospermic when compared to others. Conclusion: This study may indicate that the higher concentration of glycoprotein in seminal plasma the better quality of semen and a significant negative correlation (r=−0.749: P<0.05) were observed between seminal plasma fructose and sperm count of infertile men.